Analisis Hasil Belajar Siswa pada Pembelajaran IPA Materi Cahaya dan Sifatnya di SD 004 Padang Mutung - Aura Zakia Hadi; Dea Sifa Amalia; Naila Muthi Fatihah; Winda Nurfitri; Tia Dita Putri Latifa Yuwono (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to analyze students’ learning outcomes in science learning on the topic of light and its properties at SD 004 Padang Mutung. The study was motivated by differences in students’ understanding of science concepts, especially on abstract materials such as light and its properties. This research used a descriptive qualitative approach. The subjects of the study consisted of 3 respondents representing high, medium, and low learning outcome categories. Data were collected through observation, interviews, documentation, and students’ learning outcome data. Data analysis was conducted using data reduction, data presentation, and conclusion drawing techniques. The results showed that students’ learning outcomes were generally in the medium category with an average score of 82.14 and a standard deviation of 10.12. Students with high learning outcomes were able to understand concepts well and explain answers based on previous learning experiences, while students with low learning outcomes still experienced difficulties in understanding questions and concepts related to light and its properties. Factors affecting learning outcomes included students’ conceptual understanding, learning experiences, ability to understand questions, and the use of learning media during the learning process. The study concluded that science learning on the topic of light and its properties requires more contextual, interactive, and concrete learning activities to improve students’ conceptual understanding.